MANIPULATION OF PUBLIC CONSCIOUSNESS AS THE SOCIALLY CULTURAL PHENOMENON - Кононенко, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is about the concept of determination “manipulation of public consciouness” and the exposition of its socially cultura nature.